Enfoque QFD para diseño de servicios en el sector de hotelería en Lima-Perú - Callirgos Montoya, Lucero Alejandra (2021)
This research work will analyze the implementation of the QFD approach for the design of services in the hotel sector in Lima, Peru, in order to provide a new and improved delivery of this service, based on the growing trend of virtual commerce. In the first chapter, the formulation of the research question of the new approach to be provided by the hotel sector after the increase of e-commerce given the social confinement is presented, the description of the QFD concept, the objectives (general and specific) and the variables are also mentioned. The second chapter deals with the conceptual framework, where the important key words of the research work are mentioned; and the referential framework, which is given by the research sources used. Then, in the third chapter, the scope of the research, the collection of information through the survey and its research design are explained. Then, in the fourth chapter, the results of the survey are presented, so that, in the following chapter, the analysis and discussion of these results is carried out through the QFD matrix, together with the other sources used. Finally, this study demonstrates that there is a great business opportunity in this sector, since many current customers are opting for virtual processes and businesses; likewise, the improvements identified can be successfully implemented through the use of new technologies.